SUPORTE DE BASE DE DADOS RELACIONAL PARA APROVEITAMENTO DO IFC NO ENERGYPLUS - Ferreira, Sergio Leal (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This work presents a proposal to the relational database support for IFC appropriate in EnergyPlus. This is a major topic to help interoperability between Building Information Modeling and a wide popular and open Simulation Program.